Routine use of the Bath Adolescent Pain Questionnaire in a paediatric pain clinic. Issue 2 (May 2021) - Goddard, John M; Robinson, Jane; Hiscock, Rachel
Introduction: Assessment of outcomes from health interventions are of increasing importance, primarily to identify effective and safe treatment, but also to justify funding decisions. The Bath Adolescent Pain Questionnaire (BAPQ) is a self-report questionnaire, validated in 11–18 year olds, assessing the impact of pain in multiple domains of adolescent life. The similarly validated Bath Adolescent Pain Questionnaire for Parents (BAPQ-P) uses the same domains as the BAPQ, assessing the functioning and development of the adolescent from the parents' perspective. Methods: We conducted a prospective study, planning to routinely collect BAPQ/BAPQ-P data at initial assessment and 6 months later. All patients aged between 5 and 19 attending our chronic pain clinic for the first time between December 2009 and December 2014 were mailed BAPQ and BAPQ-P questionnaires before the first appointment and 6 months after the first appointment. Results: In total, 376 of 386 families returned questionnaires at time 0 and 96 after 6 months, 26% of those responded at time 0. We found statistically significant differences on patients' BAPQ questionnaires from 0 to 6 months showing improvement in all domains. A different result was found on parents' questionnaires where we only found a statistically significant difference on daily and emotional functioning. When comparing patient and parent questionnaires at 0 and 6 months, we found statistically significant differences between patients' and parents' questionnaires in the daily functioning and development domains. Conclusion: We believe BAPQ and BAPQ-P measurement proved useful tools to assess response to pain management input in adolescents over a 6-month period. Our experience and results suggest that these tools can, with appropriate administrative support, be used in routine clinical practice to assess patient outcomes. We also believe that BAPQ and BAPQ-P measurements have a utility to audit pain clinic activity and potentially a use in demonstrating beneficial outcomes to commissioners.